1984
DOI: 10.1111/j.1471-0528.1984.tb04747.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective controlled study of the effect on blood pressure of contraceptive preparations containing different types and dosages of progestogen

Abstract: A prospective controlled study investigated the effects of oral contraceptives on blood pressure in 485 women who were between 17 and 46 years of age and had blood pressures of < 140/90 mmHg at entry. The women were divided into seven groups depending on the chosen method of contraception: intrauterine device o r barrier method (control group): ethinyl oestradiol 3 0 p g plus levonorgestrel 150 p g (Microgynon-30 or Ovranette); norethisterone 350 p g (Micronor): norgestrel 75 pg (Neogest): norethisterone oenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
9

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 18 publications
1
24
1
9
Order By: Relevance
“…Previous studies that evaluated COCs and progestogens other than DRSP reported increased BP [13,29,30], even when contraception was provided by the nonoral route [31]. Therefore, the presence of DRSP may have contributed toward a lack of change in BP in the groups and prevented its increase, as reported by other authors [3,12,22,24,25].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Previous studies that evaluated COCs and progestogens other than DRSP reported increased BP [13,29,30], even when contraception was provided by the nonoral route [31]. Therefore, the presence of DRSP may have contributed toward a lack of change in BP in the groups and prevented its increase, as reported by other authors [3,12,22,24,25].…”
Section: Discussionmentioning
confidence: 70%
“…In normotensive patients, COCs can increase BP [8][9][10][11][12]. In addition, increases in BP levels of 4-5 mmHg have been documented with the use of COCs containing low doses of ethinylestradiol (EE) [10,13,14], and these results were confirmed by other studies using ambulatory blood pressure monitoring (ABPM) [11]. Small reductions in systolic blood pressure (SBP) (10 mmHg) and diastolic blood pressure (BP) (5 mmHg) are associated with one-to twofifths reduction in future cardiovascular disease [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies found that women using oral contraceptives have higher BPs than nonusers, but the magnitude of the differences vary, possibly reflecting differences in the populations studied and variations in the doses and types of agents used [36,37,38•,39-43,44••]. When evaluated, the effect of oral contraceptives on BP is more consistently related to estrogens than to progestational agents, whereas reports of the effects of progestogens on BP differ [40,41,43,45,46]. In some studies, progestogens reportedly have no effect on BP [43,46], although The Oral Contraceptive Study of the Royal College of General Practitioners, a prospective study, found that the incidence of hypertension increased with the duration of use and with increasing strength of the progestin [47].…”
Section: Oral Contraceptives and Blood Pressurementioning
confidence: 99%
“…Initiation of POC use immediately or within seven days after childbirth has been suggested on the grounds that (a) it would not enhance the risk of thrombosis, (b) return of ovulation may precede return of menses, and (c) women may not return for subsequent follow-up visits, and hence may become pregnant early in the postpartum period [42]. Wilson et al [43] suggested that POC use be initiated three to four weeks after delivery to avoid the increased risk of puerperal breakthrough bleeding and any possible undesirable effect on the very young infant being breastfed.…”
Section: Timing In Initiating Poc Use and Changing To Other Contracepmentioning
confidence: 99%